ANALYSIS OF MUDHARABAH FINANCING PROCEDURE TOWARDS INCREASING MUDHARABAH FINANCING IN PT. MAKASSAR BRANCH MANDIRI SHARIA BANK - nurbaeti, nurbaeti; Nuhung, Mahmud; Marhumi, St (Jurnal Ekonomi Balance, 2018)
Nurbaeti, 2016. Analysis of Mudharabah Financing Procedures for Increasing Mudharabah Financing at PT. Bank Syariah Mandiri Makassar Branch. Advisor 1: Dr. H. Mahmud Nuhung. MA and Supervisor 2: St.Marhumi, SE., MM This study aims to analyze the mudharabah financing procedure, whether by knowing the mudharabah financing procedure there will be an increase in the financing carried out in the mudharabah cooperation contract at PT. Bank Syariah Mandiri Makassar Branch. The research data was obtained by observing and interviewing directly and taken from company records / documents. The analysis technique uses qualitative and quantitative data types that use descriptive statistical analysis. The results showed that the mudharabah financing procedure has increased seen from the amount of mudharabah financing each year.